English Speaking’s Barriers of Foreign Learners - Amiruddin Amiruddin (JRTI (Jurnal Riset Tindakan Indonesia), 2022)
The ability to speak English in the era of Fourth Industrial Revolution is necessary for learners. However Gaining the ability of speaking English is still challenging for a lot of learners who live in English as Foreign Language countries.  Most of learners find it difficult to speak English due to some barriers. The objective of this study is to explore English speaking’s barriers which face by foreign learners. The method used in this study is literature research method.  To collect the data the writer used some references from articles, book, e book, and all the data related to this study. Based on the result and discussion, the writer concluded that the way of students gaining their speaking skill through learning, the exposure to English, the differences in grammar and phonology, anxiety, and motivation are some of barriers that foreign learners face in speaking English.